Information technology essentials for behavioral health clinicians - Dewan, Naakesh A.; SpringerLink (Online service). (New York Springer, 2011)
Technology will drive behavioral health innovations in efficiency and quality, this book is great primer for clinicians, students, and decision makers on how to approach technology in behavioral health? David K. Nace M.D. Vice President, Clinical Development, McKesson Health Solutions, Philadelphia, PA, USA||Information Technology is only beginning to innovate and transform the practice and performance of clinicians in behavioral healthcare. Minimal investments in information technology research and development are fundamentally altering the lives of millions worldwide. This promise and future of behavioral informatics is outlined in the chapters that follow.||Information Technology Essentials for Behavioral Health Clinicians offers an overview the entire landscape of behavioral informatics, including practical technologies and discussions regarding privacy and security. Detailed discussions also focus on the clinician, their knowledge, care, and technology developments and tools. The book then goes on to review the technologies driven by the recipient of care and concludes with a section focusing on the organization and leaderships issues involved in transforming a behavioral health care organization into modern technology supported systems of care.||The world renowned editors have crafted a book in collaboration with nationally recognized experts in the field ? physicians, psychologists, informatics executives, researchers, social workers, engineers, and sociologists ? the diversity of perspectives bringing richness to the book and making it essential reading for students and faculty in departments of psychiatry, psychology, social work, other human service disciplines, and informatics departments.
Front Matter -- Preface -- Forward -- Section 1: Overview -- Section Introduction -- Chapter 1. The Promise of Health Information Technology in Behavioral Health and Informatics: An Overview -- Chapter 2. Current Technologies for Behavioral Healthcare Clinical Practice -- Chapter 3. Ethics and Privacy of Technology and the Behavioral Health Professions.-Section 2. Clinical Practice Issues -- Chapter 4. Knowledge Delivery and Decision Support for Behavioral Healthcare Professionals -- Chapter 5. Insights on Telemedicine and Virtual Reality -- Chapter 6. Managing Care in a Pervasive Computing Environment -- Chapter 7. Improving Quality and Accountability through Information Systems -- Section 3. Patient and Client Centric Technologies Section -- Chapter 8. Social Networking, Health 2.0, and Beyond -- Chapter 9. Computerized Therapy -- Section 4. Organizational Issues -- Chapter 10. Leading Change in Implementing Technology -- Chapter 11. Evaluating the Impact of Behavioral Health Care Informatics -- Chapter 12. How Behavioral Health Care Informatics Systems Can Interface with Medical Care Systems.
Electronic reproduction.
Keywords: Mental health services; Information services; Electronic books